ОПТИМІЗАЦІЯ ДІАГНОСТИКИ ТА ЛІКУВАННЯ АТИПОВИХ ПНЕВМОНІЙ ПРИ COVID-19 - Невзгода, А. А.; Невзгода, О. А. (Українські медичні вісті, 2023)
ОПТИМІЗАЦІЯ ДІАГНОСТИКИ ТА ЛІКУВАННЯ АТИПОВИХ ПНЕВМОНІЙ ПРИ COVID-19